Parasitic Apologies. Issue 1 (2nd January 2016) - Galatolo, Renata; Ursi, Biagio; Bongelli, Ramona
Abstract : The action of apologizing can be accomplished as the main business of the interaction or incidentally while participants are doing something else. We refer to these apologies as "parasitic apologies, " because they are produced en passant (Schegloff, 2007 ), and focus our analysis on this type of apology occurring at the opening of the call. Such apologies are autonomously produced by the caller or by the call receiver, displaying the urgency to repair potential contact troubles, and find shelter inside the opening of the call, at the expense of some phases that routinely occur. The results of our analysis show interesting associations between the apologizer (the caller or the call receiver), the structure of the parasitic apology, and the impact it has on the structure of the opening sequence.